Technical and Financial Assessment of Photovoltaic Solar Systems with Bifacial Technology Comparing Four Scenarios with Different Albedos with Respect to the Base Scenario with Monofacial Technology, in a Tropical Location in Colombia - Muñoz, Yecid; De La Rosa, Miguel; Acevedo, Leidy Carolina; Velandia, Wilmer (International Journal of Energy Economics and Policy, 2023)
In photovoltaic system installations worldwide, the use of bifacial technology has begun to be more frequent due to the reduction of the cost gap associated with the manufacture of photovoltaic modules with bifacial technology compared to monofacial, encouraged by the technological maturation of bifacial modules. This research focuses on assessing the technical and financial viability of a photovoltaic solar system with bifacial technology, comparing 4 scenarios with different albedos (0.15, 0.2, 0.3 and 0.4) with respect to a base scenario that uses monofacial technology, the financial viability was evaluated according to three financial goodness criteria (NPV, IRR and Payback Time), where only in the scenario with albedo 0.4 were the costs associated with this land adaptation considered. The results of the research indicate that the most technically and financially viable scenario is the scenario with albedo 0.4, with an investment of 37,872 MCOP (3.71% more than the base scenario), an energy generated per year of 21,687 GWh/year (4.83% more than the base scenario), a net present value of 46,425 MCOP (8.42% more than the base scenario), an internal rate of return of 18.31% (1.78% more than the base scenario) and a payback time of 5.21 years (3.52% less than the base scenario).